Analysis of factors affecting the incidence of stunting in toddlers aged 6-59 months - Sadariah Sadariah; Muhammad Rifai; Muh Ilyas Nur; Musfirah Musfirah (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2023)
Stunting is a serious public health problem, especially in children under five. The causes of stunting are complex and involve a variety of factors. However, parenting that does not pay attention to nutrition, health education, feeding practices, attention, stimulation, and access to health services has been identified as significant contributors. This study aims to determine the factors that influence the incidence of stunting in toddlers aged 6-59 months. The research design is observational analytics using a case-control research design. The results showed an odds ratio (OR) value of 4.681, which means toddlers 6-59 years old with a significant parenting style will be at risk of stunting 4.68 times accompanied by a confidence interval of 95% (CI) (Cl 95%), obtained a Lower Limit (LL) value of 1.641 and Upper Limit (UL) 13.350. It can be concluded that parenting affects the incidence of stunting in toddlers aged 6-59 months. Poor parenting in nutrition, health education, feeding practices, attention, stimulation, and access to health services can contribute to the risk of stunting in early childhood. Parents need to provide proper attention and support regarding nutrition, health, and stimulation of children to support optimal growth and development